Rhythm of fetoplacental 11β-hydroxysteroid dehydrogenase type 2: fetal protection from morning maternal glucocorticoids - Lamadé, Eva; Hendlmeier, Ferdinand; Wudy, Stefan A.; Witt, Stephanie; Rietschel, Marcella; Coenen, Michaela; Gilles, Maria; Deuschle, Michael (The journal of clinical endocrinology & metabolism, 2021)
Excess glucocorticoids impact fetal health. Maternal glucocorticoids peak in early morning. Fetoplacental 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2) inactivates cortisol to cortisone, protecting the fetus from high glucocorticoids. However, time-specific alterations of human fetoplacental 11β-HSD2 have not been studied.We hypothesized that fetoplacental 11β-HSD2 activity shows time-specific alteration and acute affective or anxiety disorders impact fetoplacental 11β-HSD2 activity.In this observational study we investigated 78 pregnant European women undergoing amniocentesis (15.9 ± 0.9 weeks of gestation). Amniotic fluid was collected (8:00 to 16:30 hours) for analysis of fetoplacental 11β-HSD2 activity, using cortisol (F):cortisone (E) ratio in amniotic fluid, E/(E + F). Fetoplacental 11β-HSD2 rhythm and association with “acute affective or anxiety disorder” (patients with at least one of: a major depressive episode, specific phobia, panic disorder, generalized anxiety disorder, mixed anxiety and depressive disorder) and “acute anxiety disorder” (one of: panic disorder, generalized anxiety disorder, mixed anxiety, depressive disorder), assessed using Mini International Neuropsychiatric Interview, were investigated.Activity of 11β-HSD2 correlated with time of amniocentesis, peaking in the morning (r = −0.398; P < 0.001) and increased with acute affective or anxiety disorder (mean [M] = 0.70 vs M = 0.74; P = 0.037) and acute anxiety disorder (M = 0.70 vs M = 0.75; P = 0.016). These associations remained significant when controlling for confounders. 11β-HSD2 activity correlated negatively with pre-pregnancy body mass index (r = −0.225; P = 0.047).Our study indicates a time-specific alteration of fetoplacental 11β-HSD2 activity with peaking levels in the morning, demonstrating a mechanism of fetal protection from the morning maternal glucocorticoid surge.
Gesehen am 11.10.2021